Serological Study of Newcastle Disease in Ducks (Anas javanicus) Slaughtered in East Surabaya Traditional Market - Ardhanella, Sellianova; Damayanti, Ratna; Suwarno, Suwarno; Rantam, Fedik Abdul; Rachmawati, Kadek; Khairullah, Aswin Rafif; Rahmahani, Jola (Jurnal Medik Veteriner, 2022)
The purpose of this study was to determine the serological study of Newcastle Disease that infects slaughtered ducks (Anas javanicus) at the East Surabaya Traditional Market. This study was conducted from December 2018 to January 2019. A total of 122 samples were collected from four traditional markets in East Surabaya. The Haemagglutination Inhibition (HI) test was used to determine a positive result with an antibody titer of 4 or more. Samples for the HI test were collected from duck serum that had been treated with chicken red blood cells. The results showed 13 (10.65%) of the 122 samples were positive for ND.